PENERAPAN GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP PENINGKATAN KINERJA GURU DI SD NEGERI BELLE II (STUDI KUALITATIF) - Yefris A Selan; Patrecia Djami (Jurnal Manajemen Pendidikan, 2026)
A principal's leadership style is a crucial factor influencing teacher performance. Effective leadership can motivate teachers to deliver better performance. Not all principals are able to adapt their leadership style to different situations and conditions. As a result, the leadership style applied is ineffective in motivating and improving teacher performance. This study aims to describe the implementation of the principal's leadership style and its implications for teacher performance at Belle II Public Elementary School. The study used a qualitative approach with descriptive methods. The research subjects included the principal and teachers of Belle II Public Elementary School. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis used data reduction, data presentation, and conclusion drawing techniques. The results showed that the principal implemented a democratic, participatory, and situational leadership style. The implementation of this leadership style had a positive impact on teacher performance, as seen from increased discipline, responsibility, creativity, and the quality of learning. Thus, the principal's leadership style has an important role in improving teacher performance.